The patterns of output growth of firms and countries: New evidence on scale invariances and specificities - Carolina Castaldi; Giovanni Dosi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
This work brings together two distinct pieces of evidence concerning, at the macro level, international distributions of incomes and their dynamics, and, at the micro level, the size distributions of firms and the properties of their growth rates. First, our empirical analysis provides a new look at the international distributions of incomes and growth rates by investigating more closely the relationship between the two entities and the statistical properties of the growth process. Second, we identify the statistical properties that are invariant with respect to the scale of observation (country or firm) as distinct from those that are scale specific. This exercise proposes a few major interpretative challenges regarding the correlating processes underlying the statistical evidence.
Keywords: C10; C14; O11; 330; international distribution of income; international growth rates; firm growth; scaling laws; growth volatility; exponential tails; Wirtschaftswachstum; Einkommensverteilung; International; Betriebsgröße; Unternehmenswachstum; Statistische Verteilung; Zeitreihenanalyse; Theorie